THE INFLUENCE OF SOCIAL MEDIA-BASED ISLAMIC RELIGIOUS EDUCATION ON CHARACTER FORMATION AND MENTAL HEALTH OF UNIVERSITY STUDENTS - Muhammad Iqbal; Acep Nurullah (Karimiyah: Journal of Islamic Literature and Muslim Society, 2025)
The proliferation of social media platforms particularly Instagram and TikTok among Indonesian university students has created both extraordinary pedagogical opportunities and complex psychological risks for Islamic Religious Education (Pendidikan Agama Islam, PAI). Objectives: This study examined (i) the influence of social media-based PAI learning on character formation; (ii) its influence on student mental health; (iii) differential effectiveness of Instagram versus TikTok; and (iv) a recommended integration model. A mixed-methods sequential explanatory design was employed with 320 valid respondents drawn from four State Islamic Universities (UIN) in Indonesia via stratified random sampling. Quantitative data were analysed using Structural Equation Modelling (SEM-AMOS 24.0) and MANOVA; qualitative data from 24 purposively selected informants were processed through Braun & Clarke thematic analysis and NVivo 12. Social media-based PAI learning significantly predicted character formation (β = 0.672, p < .001) and mental health (β = 0.543, p < .001). A curvilinear effect on mental health emerged: moderate use (2–4 hours/day) was beneficial, whereas heavy use (> 5 hours/day) was detrimental (β = −0.421, p < .001). Instagram showed greater efficacy for religious and social character dimensions; TikTok excelled for moral and intellectual character. The combined-platform group achieved the highest scores on both outcomes. Character formation partially mediated the PSML–mental health relationship (indirect effect = 0.287, 95% CI [0.193, 0.389]). Social media can serve as a powerful pedagogical medium for PAI when structured through the proposed PEACE (Pedagogical, Ethical, Authentic, Creative, Evaluative) model. Institutional policies must integrate Islamic digital literacy into PAI curricula and support faculty professional development.